Effects of building resilience skills among undergraduate medical students in a multi-cultural, multi-ethnic setting in the United Arab Emirates: A convergent mixed methods study - Farah Otaki; Samuel B. Ho; Bhavana Nair; Reem AlGurg; Adrian Stanley; Amar Hassan Khamis; Agnes Paulus; Laila Alsuwaidi (PLoS ONE, 2025)
Introduction Although curricula teaching skills related to resilience are widely adopted, little is known about needs and attitudes regarding resilience training of undergraduate-medical-trainees in Middle-East-and-North-Africa-region. The purpose of this study is to investigate the value of an innovative curriculum developed through design-based-research to build resilience-skills among undergraduate-medical-trainees in the United-Arab-Emirates. Methods Convergent-mixed-methods-study-design was utilized. Quantitative data collection was through controlled random group allocation conducted in one cohort of undergraduate medical students(n = 47). Students were randomly allocated into the respective resilience-skills-building-course(study-group) versus an unrelated curriculum(control-group). All students were tested at baseline(test-1), at end of 8-week course(test-2), and again 8 weeks after end of course(test-3). Then students crossed over to the opposite course and again tested at end of 8 weeks(test-4). Testing at four timepoints consisted of questionnaires related to burnout-Maslach-Burnout-Inventory; anxiety-General-Anxiety-Disorder-7; and resilience- Connor-Davidson-Resilience-Scale. Quantitative data were analysed descriptively and inferentially. Qualitative data, constituting of students’ perception of their experience with the course, was captured using virtual-focus-group-sessions. Qualitative analysis was inductive. Generated primary inferences were merged using joint-display-analysis. Results Significant proportion of the students, at baseline, seemed to be at risk for burnout and anxiety, and would benefit from developing their resilience. There appeared to be no statistical differences in measures of burnout, anxiety, and resilience related to course delivery. Overall risk for anxiety among students increased following the COVID-19 lockdown. Qualitative analysis generated the ‘Resilience-Skills’-Building-around-Undergraduate-Medical-Education-Transitions’ conceptual model of five themes: Transitions, Adaptation, Added Value of course, Sustainability of effects of course, and Opportunities for improving course. Merging of findings led to a thorough understanding of how the resilience-skills’-building-course affected students’ adaptability. Conclusion This study indicates that a resilience-skills’-building-course may not instantly affect medical trainees’ ratings of burnout, anxiety, and resilience. However, students likely engage with such an innovative course and its content to acquire and deploy skills to adapt to changes.